Transitioning to sustainable healthy diets: A model-based and conceptual system thinking approach to optimized sustainable diet concepts in the United States - Agyemang, Prince; Kwofie, Ebenezer M.; Baum, Jamie I. (Frontiers in Nutrition, 2022)
Food production and consumption are essential in human existence, yet they are implicated in the high occurrences of preventable chronic diseases and environmental degradation. Although healthy food may not necessarily be sustainable and vice versa, there is an opportunity to make our food both healthy and sustainable. Attempts have been made to conceptualize how sustainable healthy food may be produced and consumed; however, available data suggest a rise in the prevalence of health-related and negative environmental consequences of our food supply. Thus, the transition from conceptual frameworks to implementing these concepts has not always been effective. This paper explores the relative environmental and health risks associated with highly consumed food groups and develops a methodological workflow for evaluating the sustainability of diet concepts in the context of different health, socio-economic and environmental indicators. In addition, we apply the multi-criteria decision-making techniques (an integrated Analytic Hierarchy Process- Technique for order preference by similarity to ideal solution (AHP-TOPSIS) model) to examine the health and environmental impact of selected sustainable healthy diet concepts implemented in the United States. The principal findings indicate that adopting plant-based diet patterns would benefit the environment and the population's health. However, the up-scale, broad adoption and implementation of these concepts are hindered by critical bottlenecks. Hence we propose potential modification strategies through a conceptual system thinking approach to deliver optimized sustainable diet concepts to aid in the realization of the anticipated benefits of adoption/implementation.